Fasting heat production of Saanen and Anglo Nubian goats measured using open-circuit facemask respirometry - Fernandes, M. H. M. da R. [UNESP]; Lima, A. R.C. [UNESP]; Almeida, A. K. [UNESP]; Borghi, T. H. [UNESP]; Teixeira, I. A. M. de A. [UNESP]; de Resende, K. T. [UNESP] (Wiley, 2017)
This study aimed to establish the heat production (HP) of Saanen and Anglo Nubian goats at absorptive (feeding) and at post-absorptive (fasting) statuses to determine the adequate period of fasting required for the measurement of basal metabolism. Gas exchange was recorded via open-circuit facemask respirometry. Six non-lactating and non-pregnant goats of each breed, Saanen (49.2 ± 3.2 kg of body weight, BW) and Anglo Nubian (64.0 ± 3.0 kg BW), were placed in individual pens with ad libitum access to the same total mixed ration. After a 3-day feeding period, the animals were subjected to fasting (no feed), and the gas exchange measurement was performed for 30 min at 0, 12, 20, 36, 44, 60 and 68 h after fasting. The daily HP of the Saanen and Anglo Nubian goats averaged 557.4 ± 38.7 and 357.1 ± 35.3 kJ/kg0.75 BW day respectively. During fasting, the methane production decreased exponentially in both breeds, and the critical time when methane production was statistically equal to zero was at 31 h of fasting for the Saanen goats and at 40 h for the Anglo Nubian goats. The daily HP and respiratory exchange rate during fasting decreased up to 60 h. Taken together, our results suggest that the ideal period to measure fasting heat production (FHP) for goats fed at maintenance levels should be between 40 h and 60 h of fasting. Consequently, the daily FHP, after 60 h of fasting, of Saanen and Anglo Nubian goats was 183.3 ± 16.3 and 211.1 ± 11.5 kJ/kg0.75 BW day respectively. The results presented herein are relevant for future studies of energy metabolism in goats.
Keywords: heat production; indirect calorimetry; methane; respiratory rate; ventilation